Histological modifications on Quercus suber twigs (Fagaceae) caused by the gallwasp Plagiotrochus suberi (Hymenoptera: Cynipidae). (Entomologia generalis., 2005)
Intact healthy twigs of Quercus suber were compared anatomically with twigs containing larval chambers of the gall wasp species Plagiotrochus suberi Weld 1926 using different staining techniques. A reorganisation of the tissues close to the larval chamber was found.The most important histological modifications in this zone are the presence of abnormal vessels, a higher frequency of tannin cell bundles, a higher number of cells with lipid inclusions,a highly disorganized cellular structure of the epidermis and subepidermal cortical tissues and the presence of pluriestratified epidermal invaginations. All these peculiarities are commented,compared and discussed